2020
DOI: 10.1186/s13287-020-01993-0
|View full text |Cite
|
Sign up to set email alerts
|

hPMSCs protects against d-galactose-induced oxidative damage of CD4+ T cells through activating Akt-mediated Nrf2 antioxidant signaling

Abstract: Background Mesenchymal stem cells (MSCs) were considered a regenerative therapeutic approach in both acute and chronic diseases. However, whether MSCs regulate the antioxidant metabolism of CD4+ T cells and weaken immunosenescence remains unclear. Here, we reported the protective effects of hPMSCs in aging-related CD4+ T cell senescence and identified the underlying mechanisms using a d-gal-induced mouse aging model. Methods In vivo … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
(53 reference statements)
2
12
0
Order By: Relevance
“…5 ). Similar to our findings, hPMSCs were shown to protect against oxidative damage in CD4 + T cells by activating Akt-regulated Nrf2 antioxidant signaling [ 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…5 ). Similar to our findings, hPMSCs were shown to protect against oxidative damage in CD4 + T cells by activating Akt-regulated Nrf2 antioxidant signaling [ 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…MSCs have been thought to be the source of seed cells for anti-aging biological therapeutics based on the immunomodulatory and antioxidant effects ( 29 , 30 ). Our previous research demonstrated that hPMSCs weaken D-gal induced CD4 + T cell senescence via targeting Nrf2-mediated antioxidant defenses ( 5 ). However, due to immune rejection and limited sources, MSCs are still limited in broad clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that hfPMSCs alleviate H 2 O 2 -induced cell apoptosis and oxidative stress by promoting the expression of Nrf2/Keap1/ARE antioxidant signaling ( 38 ). Our previous study found that hPMSCs played a protective effect by improving the Nrf2-mediated antioxidant pathway in senescent CD4 + T cells ( 5 ). In this study, we found that hPMSC-Exo treatment significantly increased antioxidant capacity and decreased aging-related damage and secretion phenotype in senescent CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations